Der Einfluß der Donorzahl des Lösungsmittels auf chemische und elektrochemische Vorgänge - V. Gutmann (CHIMIA, 1969)
Complex formation in donor solvents is favoured by decreasing donor number of the solvent molecules and by increasing donor number of the ligand to be coordinated. The solvation of metal ions is discussed for both hard and soft ions. It is shown that the solvation entropies are negative and contributing considerably to the free enthalpy of solvation when the metal ions are hard. The ionising properties of a solvent are shown to be related to the donor properties of the solvent molecules.